Peacemaker and Prisoner of the Past: President Nelson Mandela and South African Conflict Resolution in Southern Africa - Williams, Christopher Anthony. (Tufts University. Tisch Library., 2019)
This study examines how South Africa's negotiated transition shaped President Nelson Mandela's later peacemaking efforts throughout southern Africa. To better understand this relationship the dissertation draws on an interdisciplinary body of research that combines cognitive psychology, international relations theory and history. This research provides an explanation as to how and why seminal events (like South Africa's transition) produce "lessons" that officials later rely on when dealing with similar circumstances they find complex and challenging. The research on historical learning is combined with previously unutilized primary sources to produce case studies on South African peacemaking efforts in Lesotho, Angola and Zaire. These case studies provide a detailed look at the process of South African peacemaking, and illuminate the ways in which South Africa's own transition affected Mandela's approach to regional peacemaking. Though Mandela relied on an approach to peacemaking gleaned from South Africa's transition, he was not able to replicate his own country's success. The case studies explain the difficulties South Africa had in promoting peace throughout its region by closely examining the context of each conflict. This analysis sheds light on why Mandela's use of the lessons of South Africa's transition led to only limited success in resolving conflicts in southern Africa. In addition to addressing the relationship between South Africa's own transition and the Mandela Administration's conflict resolution efforts, the dissertations contributes to a better understanding of the human tendency to process new information through the prism of past experiences. Its findings caution policymakers to think critically and carefully on how to distil the relevant principles of peacemaking from past examples, while also acknowledging the particulars of each situation. This research also affords a new angle from which to view Nelson Mandela—one of Africa's most revered, but not necessarily well-researched statesmen. It reveals that Mandela was more than the ceremonial president he is sometimes portrayed as, and demonstrates his commitment to creating peace and stability on the African continent.; Thesis (Ph.D.)--Tufts University, 2018.; Submitted to the Dept. of Diplomacy, History, and Politics.; Advisor: Alex Waal.; Committee: Gilbert Khadiagala, Sulmaan Khan, and William Martel.; Keywords: African studies, International relations, and Cognitive psychology.